From Hysterical to Non-Criminal Psychopathic: The Histrionic Personality Disorder - Kron, Leposava (Zbornik Instituta za kriminološka i sociološka istraživanja, 2009)
In this short analysis, the author discusses phenomenology, pathogenesis and DSM-IV criteria for diagnostic assessment of histrionic personality disorder and defines some of the differential diagnostic dilemmas as well as variations of histrionic behaviour. The position of this disorder in psychopathological space could be determined by the point of convergence of hysterical and noncriminal psychopathic personality disorder.